2007
DOI: 10.1200/jco.2006.07.8972
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of an Anti-CD30 Monoclonal Antibody (MDX-060) in Hodgkin's Lymphoma and Anaplastic Large-Cell Lymphoma

Abstract: MDX-060 was well tolerated at doses up to 15 mg/kg. MDX-060 has limited activity as a single agent, but the minimal toxicity observed and the significant proportion of patients with stable disease suggests that further study of MDX-060 in combination with other therapies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(146 citation statements)
references
References 24 publications
1
137
0
8
Order By: Relevance
“…On the other hand, the overall effectiveness may be improved by patient selection based on CD52 positivity, as around half of patients present a consistent downregulation of this antigen (5,(89)(90)(91)(92). Conversely, CD30 is theoretically an optimal target for therapy owing to its minimal expression on nonmalignant cells, although the unconjugated anti-CD30 agents SGN-30 and MDX-060 demonstrated minimal effects in Hodgkin lymphoma and ALCL (93,94). However, more recently, in order to enhance the antitumor activity, the antitubulin agent monomethyl auristatin E (MMAE) was attached to a CD30-specific mAb by an enzyme-cleavable linker, producing the antibody-drug conjugate brentuximab vedotin (SGN-35) (95).…”
Section: Mabs Directed Against Surface Antigensmentioning
confidence: 99%
“…On the other hand, the overall effectiveness may be improved by patient selection based on CD52 positivity, as around half of patients present a consistent downregulation of this antigen (5,(89)(90)(91)(92). Conversely, CD30 is theoretically an optimal target for therapy owing to its minimal expression on nonmalignant cells, although the unconjugated anti-CD30 agents SGN-30 and MDX-060 demonstrated minimal effects in Hodgkin lymphoma and ALCL (93,94). However, more recently, in order to enhance the antitumor activity, the antitubulin agent monomethyl auristatin E (MMAE) was attached to a CD30-specific mAb by an enzyme-cleavable linker, producing the antibody-drug conjugate brentuximab vedotin (SGN-35) (95).…”
Section: Mabs Directed Against Surface Antigensmentioning
confidence: 99%
“…Based on promising in vitro and in vivo data [62], the drug advanced to clinical testing (Table 1). In heavily pretreated patients with relapsed or refractory CD30+ lymphomas, a multicenter phase I/II trial demonstrated a favorable toxicity profile [64]. Clinical activity was however modest, with objective clinical responses occurring in 4 of 67 HL patients.…”
Section: Unconjugated Anti-cd30 Antibodiesmentioning
confidence: 99%
“…Clinical activity was however modest, with objective clinical responses occurring in 4 of 67 HL patients. Some of these patients were taking steroids concomitantly although this was not felt to contribute to the response [64]. Additional patients had disease stabilization.…”
Section: Unconjugated Anti-cd30 Antibodiesmentioning
confidence: 99%
“…The antibodies failed to show effi cient antitumor activity (Ansell et al, 2007;Forero-Torres et al, 2009;Blum et al, 2010), but a next-generation drug-antibody conjugate, , improved the modest clinical activity of the unconjugated mAbs. This potent immunotoxin contains the antitubulin agent monomethyl auristatin E attached to SGN-30 (Ofl azoglu et al, 2008).…”
Section: Hrs Cellsmentioning
confidence: 99%